Update on Focal Infection Management: A Czech Interdisciplinary Consensus - Peřina, Vojtěch; Šmucler, Roman; Němec, Petr; Barták, Vladislav (International dental journal, 2024)
BACKGROUND: The focal infection theory has been used to explain several chronic systemic diseases in the past. Systemic diseases were thought to be caused by focal infections, such as caries and periodontal diseases, and dentists were held responsible for these diseases due to the spread of oral infections. As knowledge of the interrelationship between oral microorganisms and the host immune response has evolved over the last few decades, the focal infection theory has been modified in various ways. The relationship between oral and systemic health appears to be more complex than that suggested by the classical theory of focal infections. Indeed, the contribution of the oral microbiota to some systemic diseases is gaining acceptance, as there are strong associations between periodontal disease and atherosclerotic vascular disease, diabetes, and hospital-associated pneumonia, amongst others. As many jurisdictions have various protocols for managing this oral-systemic axis of disease, we sought to provide a consensus on this notion with the help of a multidisciplinary team from the Czech Republic. METHODS: A multidisciplinary team comprising physicians/surgeons in the specialities of dentistry, ear-nose and throat (ENT), cardiology, orthopaedics, oncology, and diabetology were quetioned with regard to their conceptual understanding of the focal infection theory particularly in relation to the oral-systemic axis. The team also established a protocol to determine the strength of these associations and to plan the therapeutic steps needed to treat focal odontogenic infections whenever possible. RESULTS: Scoring algorithms were devised for odontogenic inflammatory diseases and systemic risks, and standardised procedures were developed for general use. CONCLUSIONS: The designed algorithm of the oral-systemic axis will be helpful for all health care workers in guiding their patient management protocol.
Keywords: Focal Infection, Dental; Periodontal Diseases; konsensus; nemoci parodontu; týmová péče o pacienty; zubní kaz; Dental Caries; Consensus; Humans; Microbiota; Česká republika; Oral health; lidé; Focal infection; fokální infekce zubní; Systemic diseases; Patient Care Team; Czech Republic